Plasma rico e plaquetas (PRP) aplicado na artroplastia total do joelho - Guerreiro, João Paulo Fernandes [UNESP] (2014)
Purpose: To assess, through a clinical study, randomized, controlled ande singleblinded, the effectiveness of platelet-rich plasma in healing, pain and hemostasis after a total knee arthroplasty. Methods: 40 patients, that would be submitted to total knee arthroplasty, were selected and randomized. In 20 of these was applied platelet-rich plasma before the closure of the joint capsule. Hemoglobin and hematocrit levels were measured in the preoperative, after 24 and 48 hours of surgery. The WOMAC questionnaire and verbal pain scale were applied, measures of the range of motion of the knee were performed until the second postoperative month. Statistical analysis compared the results in order to prove if there is a difference between the groups at each time of evaluation times. Results: Hemoglobin and hematocrit levels performed preoperatively, after 24 and 48h of surgery showed no significant differences between groups (p>0,05). The WOMAC questionnaire and the measures of range of motion in the preoperative and even in the first two months also showed no statistic differences between groups (p>0,05). Pain assessement through verbal scale showed benefit in the group using platelet-rich plasma after 24 and 48 hours, one to three weeks and two months postoperative (p<0,05). Conclusions: The way it was used, the platelet-rich plasma was not effective for reducing bleeding or improve knee function after arthroplasty compared with controls. There was an advantage in the verbal scale of postoperative pain